The Authority of the Honorary Council of the Indonesian Notary Association in Imposing Sanctions for Violation of the Notary's Code of Ethics - Yani, Ahmad; qurrahman, taupiq (Veteran Law Review, 2021)
A code of ethics is a pattern of rules, procedures, signs, ethical guidelines when carrying out an activity / a job. The notary code of ethics is all moral principles that guide in carrying out the position of a notary, whether it applies to Notaries or other people who hold and carry out the position of notary public. The Indonesian Notary Association as the only forum for Notaries has a very important role in making rules and enforcing the professional code of ethics for Notaries, because one of the complementary tools in the Indonesian notary association is the presence of an Honorary Council. The Honorary Council upholds the code of ethics, dignity and dignity of the Notary, which is independent and free from partiality in carrying out its duties and authorities in the association. The objectives of this study are 1. What are the obligations and prohibitions against Notaries, 2. How is the Authority of the Honorary Council of the Indonesian Notary Association in Imposing Sanctions for Violation of the Notary's Code of Ethics in Indonesia. The methodology used in this research is normative juridical. The results of the discussion are: Notaries have obligations and prohibitions, both those regulated by law and those regulated by a code of ethics. If the notary violates the law, the notary has indirectly violated the code of ethics. However, notaries who violate the code of ethics do not necessarily violate the law. In addition, in upholding the code of ethics, the Central Honorary Council only has the authority to give warnings and proposals to the central management to make a temporary dismissal (schorsing) of association members who violate the code of ethics